MANAJEMEN PEMBERDAYAAN ANAK JALANAN (Studi pada Yayasan Rumah Singgah Anak Mandiri Lappan di Ambon) - BAKARBESSY, DEREK (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine how the management of street children's empowerment at the Ambon Lappan Children's Independent Shelter.This is a qualitative descriptive study which provides an in-depth overview of certain social symptoms found at the Ambon Lappan Children's Independent Shelter.The data source in this study is the manager of a halfway house, street children at a halfway house and an official from the Ambon City Social Welfare Office. Analysis of the data used is descriptive qualitative by quoting information then presented narratively and then interpreted and made general conclusions. The results showed that the Ambon Lappan Street Street Children 's Shelter Home in Ambon had carried out management factors including planning, implementation and evaluation. In addition, the management is flexible and is run in the coordination pa